How to measure compassion in coaches? The validation of a new scale to assess the compassion coaches’ experience towards their athletes - Oliveira, Sara (2022)
The current study aimed to validate The Compassionate Coach Scale-Coaches Version (CCS-CV) that assesses the compassion coaches’ experience towards their athletes. Two independent samples of coaches completed self-reported measures. The calibration sample (N = 196) was used to test the structure of the CCS-CV through a confirmatory factor analysis, and the validation sample (N = 287) was used to confirm its structure, through crossvalidation, and examine aspects of its validity. One higher-order factor with two lower-order factors presented an adequate fit to the data. CCS-CV demonstrated high internal consistency, convergent, discriminant, and external validity. CCS-CV is a reliable measure that allows the assessment of the compassion coaches’ experience towards their athletes and seems to be a significant contribution for practical and research fields in sports context. The present study contributes to the availability of a new instrument that allows an assessment of qualities that could be beneficial to coaches and their athletes.